ANALISIS KETEBALAN LAPISAN SEDIMEN DAN INDEKS KERENTANAN SEISMIK KOTA JAMBI BAGIAN TIMUR - Arie Satria; Ichy Lucya Resta; Nasri MZ (Engineering Faculty Universitas Lampung, 2020)
A Research was carried about analysis of sediment layer thickness and seismic vulnerability index in eastern Jambi City. The purpose of this research was to determine the effect of sediment layer thickness on seismic vulnerability index in eastern Jambi City based on microtremor data. The Acquisition data of microtremor is 25 points spread in research area. Processing data was carried out using the HVSR (Horizontal to Vertical Spectra Ratio) method to obtain the H/V curve. This curve represents the value of the natural frequency (f0) and amplification factor (A0). Based on the results of data processing obtained, the range of natural frequency (f0) value is 1.04 – 3.78 Hz, the range of amplification factor (A0) value is 1.13 - 4.88 times, the range of sediment layer thickness (h) value is 16.46 – 61.45 meters, and the range of seismic vulnerability index (Kg) value is 0.70 - 20.18×10-6 cm2/s. The results showed that the distribution of seismic vulnerability index (Kg) correlated relatively well with sediment layer thickness of the research area. The high zone of seismic vulnerability index (Kg) is relatively associated with alluvial deposits and also the sediment layer thickness of more than 30 meters. The high zone of seismic vulnerability index (Kg) is concentrated in Pasir Panjang, Tanjung Raden to Olak Kemang in Danau Teluk sub-district and Tanjung Sari in Jambi Timur sub-district.